(untitled) (Iraqi Journal of Civil Engineering, 2008)
AbstractThis study aims to investigate the properties of SCC produced by locally availablematerials , and attempts have been made to increase the range of grading of fineaggregate, with fineness modulus ranging from (1.5 to 4.1) , and to study the effect of themaximum size of coarse aggregate . It also aims to study the influence of High ReactivityMetakaolin (HRM) as a partial replacement by weight of cement on the properties of freshand hardened SCC, 24 different mixes of SCC are prepared .8 mixes are considered asReference mixes which are used for comparison purposes. To determine the workability,different test methods were adopted such as slump flow, V-funnel, and L-box tests. Whenfineness modulus of fine aggregate and maximum size of coarse aggregate increase,flowability, passing ability and segregation resistance decrease as compared with smallmaximum size of aggregate and other fineness modulus. Further more, the inclusion of10% HRM as a partial replacement by weight of cement leads to decrease flow ability andincrease of viscosity. The fineness modulus (3.1) of fine aggregate gives better resultsthan other fineness modulus. The results obtained from this study, also show that it ispossible to produce SCC from local available materials which satisfy the requirement ofthis type of concrete. Moreover, the results show the possibility of using different gradingof fine aggregate with fineness modulus ranging from (1.5 to 4.1) and the effect ofchange in fineness modulus is not significant on hardened concrete properties , while it ismore significant on fresh concrete properties .